(untitled) (CIPEEX, 2022)
AS FOOD WASTE IS ON THE RISE, CAUSING ECOLOGICAL AND SOCIETAL CONSEQUENCES,INDIVIDUALS MUST TAKE ACTION TO EASE THE ISSUE AT HAND. WITH THAT IN MIND, OUR GROUPTHOUGHT ABOUT DEVELOPING AN APP AS A SOLUTION FOR THE MATTER BY HELPING EACH PERSONKEEP TRACK OF FOOD THEY BUY AND ITS EXPIRATION DATE. THROUGH THIS INFORMATION, IT HELPSUSERS CHOOSE A VARIETY OF RECIPES THAT INCLUDES ESPECIFICALLY THE FOOD THEY HAVEAVAILABLE. WITH THE FOODLIST APP THE USER WILL BE ABLE TO CREATE HIS SHOPPING LIST TO USEAT THE MARKET, MARK WHAT HE BOUGHT, THE QUANTITY AND THE EXPIRATION DATE. WITH THISINFORMATION, THE APP WILL PROVIDE SOME MENU OPTIONS WITH THE INGREDIENTS THAT HE HAS ATHOME AVAILABLE AND WHEN SOME FOOD IS CLOSE TO THE EXPIRATION DATE, THE APPLICATION WILLSUGGEST RECIPES WITH THOSE INGREDIENTS AND INFORM THAT IT IS CLOSE TO THE EXPIRATION DATE.SO, REDUCING FOOD WASTE DUE TO LACK OF RECIPES OR FORGETTING IT IN THE FRIDGE.THE DESIGN OF THE APP WAS MADE PRIMARILY AIMING AT THE REDUCTION OF FOODWASTING, SINCE IT’S A PROBLEM THAT AFFECTS THE ENTIRE WORLD. REDUCING FOOD WASTINGMEANS A BETTER USE OF THE PRIMARY RESOURCES, REDUCTION OF GREENHOUSE EFFECT AND, INGENERAL, HELPS THE WHOLE PLANET.